KEMAMPUAN MENULIS SURAT LAMARAN PEKERJAAN SISWA KELAS XII SMK NEGERI 1 MORAMO - Harmin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
Job application letters are very useful information in laying the foundation for understanding Indonesian and at the same time a strong foundation for the formation of students' scientific character. The research problem is